THE ORDER PARAMETERS AND THEIR IMPORTANCE IN MATERIALS MODELING PROBLEMS - Hasan, B. A.; Tariq, N. H.; N. Shahid, H. R.; Ali, F. (The Nucleus, 2011)
The order/disorder phenomenon is important in many branches of science especially metallurgy and solid state physics because the transformation is accompanied by changes in many physical properties. In the last several decades many mathematical models of Order-Parameters have been proposed by the scientific community that could better describe the phenomenon. However, due to the subtle but important differences in the definition of an ‘Order Parameter’, as adopted by physicists, metallurgists, chemists, thermo-dynamists, and computer scientists an odd-complexity and abstraction has unintentionally crept in. A brief review is hereby presented of the several prevailing definitions of ‘Order Parameters’ to highlight the use of this term as it is used in materials modeling. The work of the authors is presented that is related with predicting the pair correlations for qausi-chemical treatment of binary alloy systems. The mathematical models chosen cover the range from random to ordered solid solution.